Brownfields - Martin, Sabine E. (Kansas State University, 2009)
As per EPA definition, brownfield sites are "real property, the expansion, redevelopment, or reuse of which may be complicated by the presence or potential presence of a hazardous substance, pollutant, or contaminant." It is estimated that there are up to 1 million of sites in the U.S. that fit this definition. Bringing brownfield sites back into beneficial use and at the same time reducing the utilization of greenfields for new construction, is the goal of the U.S. Environmental Protection Agency’s (EPA) brownfields program. Since 1997, the Center for Hazardous Substance Research at Kansas State University is receiving grant funding from the EPA through the TAB (Technical Assistance to Brownfields communities) program to assist communities with revitalization issues associated with their respective brownfields sites. This presentation will focus on the impacts of brownfields on communities, the importance of sustainable revitalization of these sites, and how the TAB program at KSU assists communities in doing so.
Keywords: Brownfield sites; Center for Hazardous Substance Research; Sustainability